Lifting the hood of supply and demand for trademarks of start‐ups: Partial observability estimates. (3rd August 2022) - Power, Bernadette; Reid, Gavin C.
Abstract : This paper estimates simultaneously the supply and the demand determinants of the trademark adoption decision made by start‐ups. We use a partial observability econometric model, as non‐adoption is unobserved. Estimation is by maximum likelihood using the partial observability bivariate probit (POBP) model for an unbalanced longitudinal panel of surviving US start‐ups (2004–2011). Our model is shown to provide a good explanation of supply and demand determinants of trademark adoption. For example, size, incorporation and expenditure on R&D are important on the supply side; and copyrights, licensing out and being in a high knowledge information sector are important on the demand side.